Emancipation and Enlightenment of the Human Soul According to Islamic Humanism Theory: An Analysis of Wasripin dan Satinah (Malay Literature, 2023)
Wasripin dan Satinah is a novel that reflects the political tensions of the Indonesian people during the New Order rule. Various experiences of the society are expressed primarily on issues pertaining to poverty and denial of the right to freedom of expression. In this novel, Kuntowijoyo presents the weaknesses of the government system that is based on ideology and extreme ideas. It may be observed that Kuntowijoyo strongly criticizes certain groups who are interested in dominating the lower strata of society. This paper shows the reprehensible traits and moral decay of political rulers who disregard the suffering of the people. Their governance has created differences between social classes, resulting in opposition and dissatisfaction, especially among the poor and powerless. Indeed, Wasripin dan Satinah has succeeded in presenting the emancipation and social responsibility towards the oppressed as a way to redeem the bitterness of life they had borne. Here, the author is able to shape the enlightened soul and prophetic mission in Wasripin by highlighting the element of reform to guide society towards a better direction. In fact, his work also clearly elevates his  critical stance and intellectual abilities on humanitarian issues. Thus, this paper examines Wasripin dan Satinah from the perspective of Islamic humanism by Ali Shari'ati of Iran who pioneered the ideas of liberation and reform. The finding of this study is important because it highlights the strength of Wasripin dan Satinah as a novel that is laden with strong human values.Full text: PDF